2011
DOI: 10.1099/mic.0.047555-0
|View full text |Cite
|
Sign up to set email alerts
|

The actinobacteria-specific gene wblA controls major developmental transitions in Streptomyces coelicolor A3(2)

Abstract: The Streptomyces coelicolor A3(2) sporulation gene whiB is the paradigm of a family of genes (wbl, whiB-like) that are confined to actinobacteria. The chromosome of S. coelicolor contains 11 wbl genes, among which five are conserved in many actinobacteria: whiB itself; whiD, a sporulation gene; wblC, which is required for multi-drug resistance; and wblA and wblE, whose roles had previously been little studied. We succeeded in disrupting wblA and the six non-conserved genes, but could not disrupt wblE. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 82 publications
4
93
0
Order By: Relevance
“…On the other hand, a high copy number of wblA depressed the production of ACT, RED, and CDA in S. coelicolor (and of doxorubicin in S. peucetius) (200). It was suggested that WblA mediates a switch between antibiotic production and morphological development, such that (as suggested above for WhiJ systems) mutation of wblA causes increased representation in the colony of an antibiotic-producing cell type that is intermediate between growth and a developmentally committed state (195).…”
Section: How Does Bldd Regulate Development and Antibiotic Production?mentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, a high copy number of wblA depressed the production of ACT, RED, and CDA in S. coelicolor (and of doxorubicin in S. peucetius) (200). It was suggested that WblA mediates a switch between antibiotic production and morphological development, such that (as suggested above for WhiJ systems) mutation of wblA causes increased representation in the colony of an antibiotic-producing cell type that is intermediate between growth and a developmentally committed state (195).…”
Section: How Does Bldd Regulate Development and Antibiotic Production?mentioning
confidence: 99%
“…These small, redox-and nitric oxide-sensitive iron-sulfur proteins are widespread in actinobacteria and are absent from all other bacteria (195). Disruption of wblA dramatically increased antibiotic production in S. coelicolor (195), Streptomyces peucetius (196), and Streptomyces sp.…”
Section: How Does Bldd Regulate Development and Antibiotic Production?mentioning
confidence: 99%
See 3 more Smart Citations